1996
DOI: 10.1177/001698629604000205
|View full text |Cite
|
Sign up to set email alerts
|

Wherefore Art Thou, Multiple Intelligences? Alternative Assessments for Identifying Talent in Ethnically Diverse and Low Income Students

Abstract: The recent popularity of Multiple Intelligences (MI) theory corresponds with current efforts to move away from the use of standardized measures of achievement and ability to more authentic assessment techniques, including portfolio and performance-based assessment. Gardner and his colleagues have strongly encouraged the application of MI theory to performance-based assessment. This study investigates the reliability and validity of a battery of instruments based on MI theory, including teacher checklists and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 33 publications
1
71
1
1
Order By: Relevance
“…There is some evidence to suggest, however, that they are of acceptable reliability (Plucker, Callahan, & Tomchin, 1996). Without demonstrably valid tests, however, it is difficult to evaluate the success of interventions.…”
Section: Second Wave: Domain-specific Modelsmentioning
confidence: 99%
“…There is some evidence to suggest, however, that they are of acceptable reliability (Plucker, Callahan, & Tomchin, 1996). Without demonstrably valid tests, however, it is difficult to evaluate the success of interventions.…”
Section: Second Wave: Domain-specific Modelsmentioning
confidence: 99%
“…Even though assessments exist to test Gardner's various intelligences (e.g., Gardner et al 1998), these assessments have not been associated with high levels of psychometric validity, and the evidence regarding reliability of these and similar measures is mixed (e.g., Plucker 2000;Plucker et al 1996;Visser et al 2006). (p. 814) It is interesting to compare the treatment Jensen and Gardner received from the scientific establishment for their respective work.…”
Section: A Double Standard Applied To Researchers Who Defend Hypothesmentioning
confidence: 99%
“…The aim of these studies was to confirm the presence of different types of intelligence in a battery of activities derived from Project Spectrum. Plucker, Callahan, and Tomchin (1996) performed exploratory factor analysis in order to test the existence of four types of intelligence -spatial, logical/mathematical, linguistic and interpersonal -in a sample of 1813 children in kindergarten and first grade, using the Multiple Intelligences Assessment Technique, which is based upon the assessment activities used in Project Spectrum (Gardner et al, 1998). The technique consisted of 13 performance-based activities, teacher ratings, and observational checklists corresponding to the four intelligences.…”
mentioning
confidence: 99%
“…Although these factor analysis results appear to provide some support for the theory of multiple intelligences, they are limited by the fact that they were obtained using exploratory factor analysis, rather than CFA, a much better procedure to study this issue. Pyryt (2000) reanalyzed the correlation matrix of Plucker et al (1996) to illustrate how higher-order exploratory factor analysis using more adequate procedures -maximum likelihood and direct oblimin -might be used to explain the constructs found in the initial factor analysis. Consistent with Carroll's (1993) factor analysis study of mental abilities, results indicated that the g factor underlies correlations between first-order factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation